Direct observation of the atomic density fluctuation originating from the first sharp diffraction peak in SiO2 glass - Akihiko Hirata; Shuya Sato; Motoki Shiga; Yohei Onodera; Koji Kimoto; Shinji Kohara (NPG Asia Materials)
Abstract The intermediate-range order of covalently bonded glasses has been extensively studied in terms of their diffraction peaks observed at low scattering angles; these peaks are called the first sharp diffraction peaks (FSDPs). Although the atomic density fluctuations originating from the quasilattice planes are a critical scientific target, direct experimental observations of these fluctuations are still lacking. Here, we report the direct observation of the atomic density fluctuations in silica glass by energy-filtered angstrom-beam electron diffraction. The correspondence between the local electron diffraction patterns of FSDPs and the atomic configurations constructed based on the X-ray and neutron diffraction results revealed that the local atomic density fluctuations originated from the quasi-periodic alternating arrangements of the columnar chain-like atomic configurations and interstitial tubular voids, as in crystals. We also discovered longer-range fluctuations associated with the shoulder of the FSDP on the low-Q side. The hierarchical fluctuations inherent in materials could aid in the elucidation of their properties and performance.